An Overview of the Delphi Method’s Origin, Modifications, and Use to Augment Instrument Development and Data Collection: A Research Note - Ryan W. Best; Joshua T. Campbell; M. Craig Edwards; Lauren L Cline (Journal of International Agricultural and Extension Education, 2025)
The Delphi method is well-established in agricultural and Extension education. It has been adapted to address specific research needs and is sometimes used in conjunction with other research methods to produce more robust analyses and deeper understandings of phenomena. Developed in the 1950s by the RAND Corporation, the method involves iterative rounds of questionnaires to gather experts’ opinions and reach group consensus regarding an issue or topic. Its key features include anonymity, controlled feedback, and statistical group response, which help mitigate group think. The method's adaptability has led to numerous procedural modifications, such as changes in mode of delivery, number of iterations or data collection rounds, and criteria for reaching consensus. These modifications enhanced its applicability to diverse research contexts. Despite these strengths, issues of accuracy, validity, and reliability may arise due to mistaken applications of the method. This research note aimed to clarify the Delphi method's origin and procedural standards for proper use, its evolution over time, and its service in developing instruments for additional data collection and analysis. By applying the Borich (1980) model to findings derived from a Delphi study, as described in this note, gaps in urban Extension educators’ competencies were not only identified but also prioritized for professional development offerings. This underscores the method's versatility and potential as a foundational step in conducting social science research that prizes the input of experts. Future research should explore other data collection approaches the Delphi method could complement as researchers pursue more robust, reliable, and actionable results.
Keywords: expert opinion; group consensus-building; research methodology